Vpliv strategije trajnostnega inoviranja proizvodnih procesov na menedžment odpadne tehnološke vode - Krajnc, Bojan (Revija za univerzalno odličnost, 2025)
Research question (RV): How do sustainable innovation strategies for production processes affect the management of wastewater processes? Purpose: The purpose of the research was to conduct a systematic review of domestic and foreign professional literature by authors who discussed various types of process innovations that affect environmental aspects, especially in the management of process wastewater. Method: Using a quantitative scientific research approach, we conducted a systematic review of domestic and foreign professional literature, which we searched in publicly available databases. We used the search terms "sustainable innovation for production processes" and "process wastewater" and their English equivalents in the search. We included articles published between 2020 and 2024 in systematic analysis and reviewed a total of 110 empirical studies. Among them, we highlighted 30 key studies that were relevant to our research area. All collected material was archived and selectively analyzed, paying special attention to the sources that were most important for our research. For data processing, we used the method of description and compilation of the results of qualitative and quantitative research. Results: The conclusions of research by various authors highlight a wide range of factors that influence strategies, sustainability, innovation, production processes and management of technological wastewater. Research on sustainable practices of organizations shows that these organizations often focus on compliance with environmental regulations, creation of sustainable value chains and development of innovative sustainable products and processes. Despite the extensiveness of the studies analyzed on sustainable development, we conclude that no research has yet been conducted in which all four factors (strategy, sustainability, innovation, production processes) should be considered, especially in relation to technological wastewater management. This indicates the need for further research into these factors and the adaptation of practices to achieve optimal results. Organization: Studying sustainable innovation strategies for production processes enables organizations to better integrate sustainable practices and innovations, which brings competitive advantage and greater adaptability. This strengthens environmental and social responsibility, optimizes processes, and improves the organization's performance and market position. Society: Organizations with sustainable practices and innovations contribute to a more responsible, efficient, and sustainably oriented society, which promotes long-term economic and environmental development. Originality: Despite the growing recognition of the link between innovation and sustainable development, the relationship between these two concepts remains unclear in literature. We also highlight a gap in research on how different types of innovation affect environmental aspects, especially in the management of wastewater. Limitations/further research: We focused on 30 studies conducted between 2020 and 2024, and based on their findings, we made suggestions for further research.
Keywords: inovacije; menedžment; odpadna tehnološka voda; organizacija; procesi; strategije; trajnost